Influence of light-curing units and restorative materials on the micro hardness of resin cements - Kuguimiya Rosiane; Alves Luciana; Seabra Flavio; Sarmento Carlos; Santos Alex Jose; Machado Claudia (Wolters Kluwer Medknow Publications, 2010)
Aim: The aim of this study was to evaluate the effect of indirect restorative materials (IRMs) and light-curing units (LCUs) on the micro hardness of dual-cured resin cement. Materials and Methods: A total of 36 cylindrical samples (2 mm thick) were prepared with dual-cured resin cement (Relyx ARC) photo-activated with either a QTH (Optilight Plus) for 40s or a LED (Radii) light-curing unit for 65s. Photo-activation was performed through the 2-mm- thick IRMs and the samples were divided into six groups (n=6) according to the combination of veneering materials (without, ceramic and indirect resin) and LCUs (QTH and LED). In the control group, the samples were light-cured with a QTH unit without the interposition of any restorative material. Vickers micro hardness test was performed on the top and bottom surfaces of each sample (load of 50 g for 15 secs). The data were statistically analyzed using a three-way ANOVA followed by Tukey x s post-hoc test ( P < 0.05). Results: There were no statistically significant differences on the top surface between the light curing-units ( P > 0.05); however, the LED provided greater hardness on the bottom surface when a ceramic material was used ( P < 0.05). The mean hardness in photo-activated samples, in which there was no interposition of indirect materials, was significantly greater ( P < 0.01). Conclusions: It may be concluded that the interposition of the restorative material decreased the micro hardness in the deeper cement layer. Such decrease, however, was lower when the ceramic was interposed and the cement light-cured with LED.